PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN LEVERAGE TERHADAP PERATAAN LABA - Rianto -; Rizka Yudinur (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2022)
This research was conducted on basic and chemical industrial sector companies listed on the Indonesia Stock Exchange. The purpose of this study is to analyze the effect of Profitability, Firm Size and Leverage on Income Smoothing (empirical study on basic and chemical industrial sector companies listed on the Indonesia Stock Exchange for the period 2016-2020). The population in this study amounted to 69 basic and chemical industrial companies on the Indonesia Stock Exchange. The sampling technique used is purposive sampling, obtained a sample of 29 companies. The type of data used is secondary data sourced from the official website www.idx.co.id. The analytical method used in this research is logistic regression analysis. Based on the results of this study, it can be seen that profitability as measured by ROA has no effect on income smoothing, company size has a negative effect on income smoothing, leverage has no effect on income smoothing as measured by the debt to equity ratio (DER).